POWER CONVERTER FOR ROLLING STOCK - TAKAGI TAKASHI (2015)
PROBLEM TO BE SOLVED: To achieve reduction in size and cost of an apparatus, even when a boost circuit is provided in order to increase the motor voltage.SOLUTION: A first power conversion circuit of a power converter for rolling stock receives a DC power supplied from a DC overhead line via a DC reactor, and functions as a step-up chopper circuit, to perform DC-DC power conversion by switching operation of a plurality of semiconductor elements, and a first power circuit boosts the voltage higher than the specified voltage of the DC power supplied from the DC overhead line. A second power conversion circuit performs DC-AC power conversion of the DC output power from the first power conversion circuit by switching operation of a plurality of semiconductor elements, and outputs to a corresponding AC motor. A heat receiving member is attached so that a semiconductor element can be coupled thermally, and receives heat. 【課題】モータ電圧を増加させるために昇圧回路を設ける場合でも、機器の小型化、低コスト化を図る。【解決手段】実施形態の鉄道車両用電力変換装置の第１電力変換回路は、直流架線から供給される直流電力が直列リアクトルを介して入力され、昇圧チョッパ回路として機能して、複数の半導体素子のスイッチング動作により直流−直流電力変換を行い、第１電力回路は、直流架線から供給される直流電力の規定電圧よりも高い電圧に昇圧する。第２電力変換回路は、第１電力変換回路の出力直流電力を複数の半導体素子のスイッチング動作により直流−交流電力変換を行い対応する交流電動機に出力する。受熱部材は、半導体素子が熱的に結合可能に取り付けられて、受熱する。【選択図】図１